Negotiating accuracy and authenticity in an Aboriginal King Lear. Issue 2 (3rd April 2017) - Dean, David
Abstract: This article considers the negotiations surrounding historical authenticity in a unique Canadian production of Shakespeare's King Lear . It argues that choices had to be made between accuracy on the one hand and authenticity on the other. Three particular contexts of these negotiations about authenticity are identified: that of Shakespeare's original play, the production's chosen setting of early modern 'Canada', and contemporary Canadian society and politics. Traced through the National Art Centre English Theatre Company's script work, set and costume design, and dramaturgy, the article invites a re-consideration of the relationship between a commitment to historical accuracy and a desire to achieve historical authenticity.